2021
DOI: 10.1093/ajhp/zxab208
|View full text |Cite
|
Sign up to set email alerts
|

Providing essential clinical pharmacy services during a pandemic: Virtual video rounding and precepting

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“… 30 35 36 44 50 58 61 A number of PC-eHealth service models was also pertained with an integration of the electronic medical record (EMR) system. 21 22 30 31 37 42 47 57 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 30 35 36 44 50 58 61 A number of PC-eHealth service models was also pertained with an integration of the electronic medical record (EMR) system. 21 22 30 31 37 42 47 57 …”
Section: Resultsmentioning
confidence: 99%
“…The impact of adoption eHealth in PC during the pandemic was mainly in reducing the need for physical contact or visits to the hospital/clinic for minimising the risks of infection and transmission 20 21 25 26 28 30 32 33 38 43 45 48 52–54 58 60 62 as well as allowing the continuous monitoring of the patients in the absence of in-person interactions. 21 23 26 27 29–31 39–43 45–47 49 51 56 57 Some studies reported an improvement in the efficiency of PC due to the use of eHealth 25 34 38 44 50 57 58 61 and patient satisfaction about the PC-eHealth services they received was also reported. 28 29 32 36 37 44 46 54 59 Other benefits of adopting eHealth in PC during the pandemic included the dissemination of reliable information, 24 reduced abuse of over-the-counter medicines, 35 facilitating transition of care between hospitals 22 and communications within the healthcare team and with patients and caregivers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these challenges, numerous opportunities have elicited the critical role of clinical pharmacists in pandemics and public healthcare emergencies (Table 2). Some major examples in the inpatient setting included the utilization of advanced technology to provide remote counseling to healthcare providers (telehealth services), remote therapeutic drug monitoring (TDM) (telemonitoing) of hospitalized patients, and virtual rounding (Aburas et al, 2020;Allison et al, 2021;Arain et al, 2021;Aruru et al, 2021;Bhat and Kehasse, 2020;Danelich et al, 2021;Herzik et al, 2021;Li et al, 2021;Marchese et al, 2021;Meng et al, 2020;Muflih et al, 2021;Song et al, 2021;Surapat et al, 2021;Thomas et al, 2021;Wieruszewski et al, 2021;Zheng et al, 2021;Zhou et al, 2021). One hospital described a technology named Connect Care Pro, which was utilized during the pandemic (Kjerengtroen et al, 2020).…”
Section: General Clinical Pharmacistsmentioning
confidence: 99%